The role of parents and teachers' teaching styles on the learning achievement of islamic religious education at sabuk empat state elementary school - Sinta Larasati; Putri Maharani Pratiwi; Wisna Meri; Ahmad Syarifuddin Zuhri; Supriyanti (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
Islamic Education plays an important role in shaping the character and personality of students from an early age. At the elementary school level, PAI serves as the main means of instilling spiritual values and praiseworthy morals. Learning achievement in PAI subjects is influenced by several factors, one of which is the involvement of parents in assisting the child's educational process at home. In addition, the way teachers teach also has a big role in determining student success. Teachers who are able to deliver material with varied methods, use appropriate learning media, and invite students to be actively involved in learning activities can create an effective and enjoyable learning environment. This study aims to examine the extent to which the role of parents in supporting student learning at home, as well as how the teacher's teaching style in delivering PAI material can have an impact on student learning achievement. Using a qualitative approach and case study method, data were collected through observation, in-depth interviews, and documentation. The results revealed that the active involvement of parents at home as well as the teacher's ability to adjust the teaching style to the needs of students greatly influenced the success of PAI learning. Therefore, the synergy between parents and teachers is a key factor in improving student learning achievement.